NUMERICAL STUDY ON 3-D LIGHT AND HEAT TRANSPORT IN BIOLOGICAL TISSUES EMBEDDED WITH LARGE BLOOD VESSELS DURING LASER-INDUCED THERMOTHERAPY - Zhou, Jianhua; Liu, Jing (Numerical heat transfer. Part A, Applications, 2004)
Tissue vasculature plays an important role in the temperature responses of biological bodies subject to laser heating. For example, interfaces between blood vessel and its surrounding tissues may lead to reflection or absorption of the coming laser light. However, most of the previous efforts just treat this by considering a collective model. To date, little attention has been paid to the effect of a single blood vessel on tissue temperature prediction during laser-induced thermotherapy. To resolve this important issue in clinics, we propose to simultaneously solve the three-dimensional (3-D) light and heat transport in several typical tissue domains with either one single blood vessel or two countercurrent blood vessels running through. Both surface and intervenient laser irradiations are considered in these studies. The 3-D heat transfer and blood flow models are established to characterize the temperature transients over the whole area. Coupled equations for heat and blood flow in multiple regions are solved using the blocking-off method. In particular, the Monte Carlo method is introduced to calculate the light transport inside the tissues as well as the blood vessel. Theoretical algorithms to deal with the complex interfaces between the tissues and vessels, and the tissue-air interface, are given. The heat generation pattern due to absorption of laser light is thus obtained by Monte Carlo simulation and then adopted into the heat and flow transport equations to predict the 3-D temperature transients over the whole domain. It is demonstrated that without considering large-size blood vessels inside the tissues, a very different temperature response is induced when subject to the same laser heating. Detailed temperature developments for the aforementioned vessel configurations are comprehensively analyzed. Implementation of the laser irradiation pattern to the clinical practices is discussed. We also test the effects of the buoyancy-driven blood flow due to laser heating on the tissue temperature response. This study may raise new issues to evaluate the contribution of a single blood vessel in modeling laser-tissue interaction. Such information is expected to be critical for accurate treatment planning in clinics.